2010
DOI: 10.1091/mbc.e09-06-0534
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Translocation of β-Actin Is Involved in Transcriptional Regulation during Macrophage Differentiation of HL-60 Cells

Abstract: The functional significance of nuclear translocation of β-actin remains unclear. Here, we demonstrate that PMA induces β-actin accumulation in the nucleus and binding to various target genes with different functions. We also find that accumulated nuclear β-actin is involved in recruitment of RNA polymerase II and in transcription regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
69
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 48 publications
7
69
0
Order By: Relevance
“…Because our export FLIP experiment showed that the availability of actin monomers is limiting nuclear export rates of actin, this also suggests that increased binding of actin to nuclear structures, e.g., upon transcriptional activation, would increase the levels of nuclear actin. Accordingly, transcriptionally quiescent cells have less nuclear actin (22) and differentiating, transcriptionally active macrophages display increased actin in their nuclei (23), supporting the idea that an interesting feedback-loop may exist between nuclear actin levels and transcriptional activity of the cell. Indeed, decreased nuclear actin in Ipo9-depleted cells resulted in reduction on 5-FUrd incorporation into nascent transcripts (Fig.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Because our export FLIP experiment showed that the availability of actin monomers is limiting nuclear export rates of actin, this also suggests that increased binding of actin to nuclear structures, e.g., upon transcriptional activation, would increase the levels of nuclear actin. Accordingly, transcriptionally quiescent cells have less nuclear actin (22) and differentiating, transcriptionally active macrophages display increased actin in their nuclei (23), supporting the idea that an interesting feedback-loop may exist between nuclear actin levels and transcriptional activity of the cell. Indeed, decreased nuclear actin in Ipo9-depleted cells resulted in reduction on 5-FUrd incorporation into nascent transcripts (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…It remains to be determined how global the actin-dependent transcriptional repression is or whether some genes are affected more than others. The latter seems more plausible, because the lack of nuclear actin has already been shown to regulate the specific fluctuations in gene expression required for the normal function of certain epithelial cells (22) and cellular differentiation specifically accumulates actin on certain promoters (23). In Drosophila, the DNA adenine methyltransferase identification technique has revealed that actin is found associated with a special type of euchromatin, which is linked to tissue-specific gene expression (47), further suggesting that actin may have genespecific effect on transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent more systematic study using ChIP-on-chip mapped the recruitment of actin to gene promoters in response to phorbol 12-myristate 13-acetate (PMA)-induced differentiation of HL-60 cells towards macrophages. This study found that in unstimulated cells only few promoters contained actin, but upon stimulation with PMA over 800 genes, with variable functional annotations, displayed enriched binding by actin [Xu et al, 2010]. Curiously, actin has also been found on intragenic regions of at least rDNA [Ye et al, 2008], however, the functional role of actin at these sites is not obvious.…”
Section: Connecting Actin To Rna Polymerasesmentioning
confidence: 81%
“…PMA is used to induce macrophage differentiation in several human monocytic cell lines. THP-1 (human monocytic leukemia cell line), HL-60 (human promyelocytic leukemia cell line) and U937 (human histiocytic lymphoma cell line) change their characters including morphology and phagocytic activity from monocyte-like rather into macrophagelike [17,21,23,25]. Human PBMC-derived monocytes were also reported to differentiate into macrophage, although morphological and functional analysis was not performed [23].…”
Section: Discussionmentioning
confidence: 99%